Assessment of the non-lactic acid bacteria microbiota in fresh cucumbers and commercially fermented cucumber pickles brined with 6% NaCl. (February 2019) - Pérez-Díaz, Ilenys M.; Hayes, Janet S.; Medina, Eduardo; Webber, Ashlee M.; Butz, Natasha; Dickey, Allison N.; Lu, Zhongjing; Azcarate-Peril, Maria A.
Abstract: Limited documentation of the cucumber fermentation microbiome has impeded the understanding of the role of microbes on the quality of finished products. We characterized the microbiome of fresh and fermented cucumber samples using culture dependent and independent techniques, with an emphasis on the non-lactic acid bacteria (non-LAB) population. Insubstantial microbiome variations were observed among fresh cucumber types with Rhizobium (31.04%), Pseudomonas (14.08%), Pantoea (9.25%), Stenotrophomonas (6.83%), and Acinetobacter (6.5%) prevailing. The relative abundance of LAB remained below 0.4% and 4.0% on fresh cucumbers and day 3 of the fermentations brined with 6% sodium chloride, respectively. Fermentation cover brine samples collected on day 1 harbored Pseudomonas, Pantoea, Stenotrophomonas, Acinetobacter, Comamonas, Wautersiella, Microbacterium, Flavobacterium, Ochrobactrum and the Enterobacteriaceae, Citrobacter, Enterobacter and Kluyvera . Plate counts for presumptive Klebsiella and Pseudomonas from fermentation cover brine samples reached 2.80 ± 0.36 and 2.78 ± 0.83 log of CFU/mL, respectively, in 30% and 60% of the nine tanks scrutinized with selective media. Both genera were found in cover brine samples with pH values at 4.04 ± 0.15. We aim at elucidating whether the low relative abundance of non-LAB in commercial cucumber fermentations, in particular Pseudomonas and Enterobacteriaceae, impacts the quality of fermented cucumbers. Highlights: Characterization of the microbiota in fresh and brined cucumbers. Isolation of Pseudomonas and Enterobacteriaceae from cucumber fermentations. Ochrobactrum, Citrobacter, Klebsiella and Kluyvera in cucumber fermentations.